Economic Management Strategies in Virtual Platforms and the Metaverse - Razak, Farhat Abdul; al-Ikhsan, Hussein; Sriasih, Sutriani Dewi; Nafir, Mohammad Akbar; Hilal , Fikri (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The metaverse has emerged as a new domain within the digital economy, offering decentralized and participatory ecosystems driven by digital assets such as NFTs, tokens, and cryptocurrencies. Platforms like Decentraland, Roblox, and The Sandbox represent varied models of economic governance and user engagement. However, effective economic management strategies in these virtual environments remain underdeveloped. This study explores how the three platforms manage digital economies, focusing on asset governance, community incentives, and risk dynamics. Using an exploratory qualitative approach, data were collected through semi-structured interviews and document analysis, and then thematically analyzed using NVivo software. Results show decentraland emphasizes DAO-based transparency, Roblox relies on centralized monetization, and The Sandbox balances both in a hybrid model. The study concludes that successful economic strategies in the metaverse require integrating governance structures, incentive mechanisms, and social user interaction. These findings offer insights for building more adaptive, inclusive, and sustainable digital economic frameworks in virtual ecosystems.